CHALLENGES IN IMPLEMENTING A PATIENT-CENTERED CARE WORK CULTURE IN THE INPATIENT WARD OF RSUD KETAPANG SAMPANG - Sukarno Sukarno; Ansarul Fahrudda; Muhammad Anas (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Patient-Centered Care (PCC) is increasingly evaluated alongside clinical accuracy, especially in inpatient wards where interactions and coordination demands are intensive. This study analysed challenges in implementing a PCC-oriented work culture in the inpatient ward of RSUD Ketapang Sampang, focusing on communication, patient/family involvement, interprofessional coordination, and contextual factors shaping everyday care. Using a qualitative Interpretative Phenomenological Analysis (IPA) design, data were collected through semi-structured in-depth interviews with two participant groups (health professionals and inpatients and/or accompanying family members), supported by field observations and relevant document review. Analysis followed IPA stages from repeated reading and initial noting to emergent and cross-case theme development, with rigor enhanced through triangulation, member checking, and an audit trail. Findings indicate that PCC is understood as a service orientation that respects patients as persons, yet its relational expression often narrows when workload intensifies and routines become task-driven. Patient and family involvement was present but did not consistently translate into shared decision-making, and was frequently experienced as receiving information rather than dialogue and clarification. The consistency of patient experiences was shaped by handovers, authority boundaries, and the extent to which interprofessional coordination became visible as coherent communication to patients/families. PCC practices strengthened when supported by key figures and clear work supports, but sustainability remained uneven across shifts and staff.